Water production functions for Central Plains crops - Trout, Thomas J., author; Bausch, Walter C., author (Colorado State University. Libraries, 2012)
Sustaining irrigated agriculture with limited water supplies requires maximizing productivity per unit of water. Relationships between crop production and water consumed are basic information required to maximize productivity. This information can be used to determine if deficit irrigation is economically desirable and how to best manage limited water supplies. Field trials of corn, sunflower, dry bean, and wheat production with six levels of water application were used to develop water production functions based on consumptive use and to better understand water timing effects and crop responses to stress. Initial results indicate linear relationships between yield and crop ET. The field data are being used to improve and validate crop models so they can be used to generalize the field results for other climate and soil characteristics.
Proceedings of the 24th annual Central Plains irrigation conference
Presented at Proceedings of the 24th annual Central Plains irrigation conference held on February 21-22 in Colby, Kansas.